2010
DOI: 10.1002/cncr.25760
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of Nm23‐H1 in head and neck squamous cell carcinoma is associated with radiation resistance

Abstract: BACKGROUND: Although radiation resistance is a primary issue in radiation therapy, attempts to find predictors of radiation resistance have met with little success. The authors therefore aimed to determine predictors for radiation resistance to improve the prognosis of head and neck squamous cell carcinoma (HNSCC). METHODS: HNSCC cell lines, SCC15, SCC25, and QLL1, irradiated with an acute dose of 4 grays (Gy) (RR-4), a cumulative dose of 60 Gy (RR-60), and a booster dose of 4 Gy over 60 Gy (RR-60 þ 4), were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Phosphorylated FAK is involve in activation of many signal transduction molecules and affects several cellular biological behaviors (She et al, 2010). Over expression of Nm23-H1, specifically its nuclear translocation may be a powerful predictor of radiation resistance in head and neck squamous cell carcinoma (HNSCC) (Park et al, 2010). Understanding the Nm23 gene expression could develop an effective method for targeting metastatic cascade and inhibition of tumor progression that could be a novel potential therapeutic strategy for cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylated FAK is involve in activation of many signal transduction molecules and affects several cellular biological behaviors (She et al, 2010). Over expression of Nm23-H1, specifically its nuclear translocation may be a powerful predictor of radiation resistance in head and neck squamous cell carcinoma (HNSCC) (Park et al, 2010). Understanding the Nm23 gene expression could develop an effective method for targeting metastatic cascade and inhibition of tumor progression that could be a novel potential therapeutic strategy for cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Seven oral cancer cell lines- SCC25, QLL1 (From Dr. Park, Yonsei University College of Medicine, Korea [23] & Dr Rheinwald, Harvard Medical School, Boston [24] ); UPCI:SCC029B, UPCI:SCC040 & UPCI:SCC074 (From Dr. S Gollin, University of Pittsburgh, PA) [25] ; AW8507 & AW13516 [26] were used in the study. Additionally an immortalized Fetal Buccal Mucosa (FBM) [27] and a Dysplastic Oral Keratinocyte (DOK) (from Dr. Ken Parkinson, Queen Mary's School of Medicine & Dentistry, UK) [28] cell lines were also used in study.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally an immortalized Fetal Buccal Mucosa (FBM) [27] and a Dysplastic Oral Keratinocyte (DOK) (from Dr. Ken Parkinson, Queen Mary's School of Medicine & Dentistry, UK) [28] cell lines were also used in study. The cells were maintained in MEM or IMDM supplemented with 10% FBS & 1% standard antibiotic mixture in 5% CO 2 incubator at 37°C as described earlier [17] , [23] , [29] .…”
Section: Methodsmentioning
confidence: 99%
“…Sheng and coworkers suggested that NME1 enters the nucleus after DNA damage and possibly takes part in several DNA-repair mechanisms [64]. It has even been suggested by Park and coworkers that the nuclear localization of NME1 in head and neck squamous cell carcinoma could be associated with radiation resistance [67] and, therefore, serve as a strong radiation resistance predictor. Similar research has been reported on human nasopharyngeal carcinoma [68] and oral squamous cell carcinoma [69].…”
Section: Nme1 and Nme2 Translocate To The Nucleus After Gamma Irradiamentioning
confidence: 99%